CHEMICAL AND FUNCTIONAL CHARACTERIZATION OF ANTIMICROBIAL METABOLITES ISOLATED FROM THE ASCIDIAN RHOPALAEA BIRKELANDI - Cordero, Maribel (2011)
Marine ecosystems have a very large diversity of resources, most of them still partially unknown, and a few others exploited for development of new industrial and toxicological products. The objective of this investigation was to determine whether the acetone extract of the ascidia R. birkelandi from the Pacific coast of Costa Rica showed qualitative antimicrobial activity against the S. aureus bacteria and the G. candidum fungus, and to verify their main secondary metabolites in the active extract using chromatographic and spectroscopic techniques. Ascidians were collected at Tambor, Guanacaste, Costa Rica, between December 2007 and March 2008. Activity against the Gram positive bacteria and fungi was evaluated using ethanolic (95%) and acetonic extracts. Both extracts showed activity against G. candidum; however, only the acetonic extract showed activity against S. aureus. A coumarin and a hydroxyanthraquinone were isolated from a crude extract of R. birkelandi as metabolites present in the active fraction. Purification and isolation were performed by chromatographic techniques and solid phase extraction. Structural information was obtained by spectroscopic analyses: Ultraviolet (UV-Visible), Fourier Transform Infrared (FT-IR), Liquid Chromatography Tandem Mass Spectrometry (LC/MS/MS), Gas Chromatography Mass Spectrometry (GC/MS), Proton Nuclear Magnetic Resonance (1HNMR), and Carbon-13 Magnetic Resonance (13C-NMR). Further studies are recommended for characterization and quantification of the active components of this extract and the possible elucidation of the mechanisms of action.